L1 CELL ADHESION MOLECULE (L1CAM) AND PHOSPHORYLATED FIBROBLAST GROWTH FACTOR RECEPTOR 1 (PFGFR1) EXPRESSION POSITIVELY CORRELATES WITH NEUROLOGICAL MALIGNANCIES. (3rd October 2018) - Egbivwie, Naomi; Cook, Siân; Cockle, Julia; Esteves, Filomena; Short, Susan C; Ismail, Azzam; Humphries, Matthew P; Brüning-Richardson, Anke
Abstract: INTRODUCTION: Gliomas are intrinsic brain tumours characterised by their highly invasive, malignant and aggressive nature. Persistently poor prognoses highlight the urgent clinical need to identify novel approaches and therapeutic targets to improve glioma management. Recently we reported a correlation of fibroblast growth factor receptor 1 (FGFR1) expression with malignancy, tumour grade and location in paediatric gliomas. There is evidence that the L1 cell adhesion molecule (L1CAM) potentiates FGFR1 signalling. L1CAM is a transmembrane glycoprotein associated with poor clinical outcomes in various cancers promoting cell motility. Here, following our initial studies on FGFR1, we investigated FGFR1 in its activated phosphorylated form (pFGFR1) as well as L1CAM expression in our cohort and association with various clinicopathological parameters. METHODS. A commercially available tissue microarray (CNS2081, US Biomax) was stained for pFGFR1 and L1CAM expression and data was scored using manual and digital assessment (QuPath). Scores were separately dichotomised into low and high L1CAM and pFGFR1 expression using the median value in SPSS. A two-sided Pearson's chi squared statistical test was performed using GraphPad Prism where p<0.05 was considered statistically significant. RESULTS. There was higher L1CAM expression in malignant tumours compared to benign tumours (p<0.05). There was higher L1CAM expression in tumours located in the cerebellum compared to the cerebrum (p<0.05). Both L1CAM and pFGFR1 expression was predominantly localised to the cytoplasm. DISCUSSION: Our results suggest that L1CAM expression is associated with malignancy. Most high-grade astrocytomas exhibited pFGFR1 cytoplasmic expression suggesting that the FGFR1 pathway is activated, which is known to be associated with cell migration and aggressive tumours. L1CAM expression was found in all tumours which suggests a role in glioma tumourigenesis. Further research on pFGFR1 and L1CAM interaction is warranted in a larger clinical cohort. pFGFR1 and L1CAM may be potentially useful biomarkers and good candidates for therapeutic intervention